Long‐term urbanization impacts the eastern golden frog (Pelophylax plancyi) in Shanghai City: Demographic history, genetic structure, and implications for amphibian conservation in intensively urbanizing environments. (7th November 2020) - Wei, Xu; Huang, Meiling; Yue, Qu; Ma, Shuo; Li, Ben; Mu, Zhiqiang; Peng, Chuan; Gao, Wenxuan; Liu, Wenli; Zheng, Jiaxin; Weng, Xiaodong; Sun, Xiaohui; et al.
Abstract: Understanding the mechanisms of how urbanization influences the evolution of native species is vital for urban wildlife ecology and conservation in the Anthropocene. With thousands of years of agriculture‐dominated historical urbanization followed by 40 years of intensive and rapid urbanization, Shanghai provides an ideal environment to study how the two‐stage urbanization process influences the evolution of indigenous wildlife, especially of anuran species. Therefore, in this study, we used mitochondrial Cyt‐b gene, microsatellite (SSR), and single nucleotide polymorphism (SNP) data to evaluate the demographic history and genetic structure of the eastern golden frog ( Pelophylax plancyi ), by sampling 407 individuals from 15 local populations across Shanghai, China. All local populations experienced bottlenecks during historical urbanization, while the local populations in urban areas maintained comparable contemporary effective population sizes ( N e ) and genetic diversity with suburban and rural populations. Nevertheless, the rapid modern urbanization has already imposed significant negative effects to the integrity of populations. The 15 local populations were differentiated into eight genetic clusters, showing a spatial distribution pattern consistent with the current urbanization gradient and island–mainland geography. Although moderate gene flow still occurred from the rural peripheral cluster to urban and suburban clusters, population fragmentation was more serious in the urban and suburban populations, where higher urbanization levels within 2‐km radius areas showed significant negative relationships to the N e and genetic diversity of local populations. Therefore, to protect urban wildlife with limited dispersal ability, improving conditions in fragmented habitat remnants might be most essential for local populations living in more urbanized areas. Meanwhile, we highlight the need to preserve large unfragmented rural habitats and to construct corridor networks to connect discrete urban habitat remnants for the long‐term wildlife conservation in intensively urbanizing environments.